Familial clustering of type 1 diabetes onset induced by COVID-19: case report - Alshehri, Norah Ali (Journal of the Pakistan Medical Association, 2026)
Type 1 diabetes (T1D) is a complex disorder with a genetic component that affects families due to heritable factors, such as polymorphisms in the human leukocyte antigen (HLA) region, as well as environmental triggers. Recent evidence suggests that viral infections, particularly coronavirus disease 2019 (COVID-19), may increase the risk of developing T1D. This case report presents a 24-year-old woman and her siblings who developed T1D a few months after recovering from COVID-19. The patient presented with acute hyperglycaemia, markedly elevated HbA1c levels, and glutamic acid decarboxylase 65 (GAD-65) autoantibodies indicating an autoimmunity. This case suggests that the COVID-19 pandemic may have accelerated autoimmune destruction of pancreatic Beta cells and demonstrates the urgent need to implement genetic counselling and autoantibody screening in individuals at risk. The reports highlight the need for further studies to explore the association between viral infection and T1D pathology on one hand, and public health measures for the prevention of COVID-19 on the other hand. Keywords: COVID-19, Type 1 diabetes, Familial.